Silkworm loose egg preparation, incubation, black boxing, transportation, and brushing - Singh, G B (Indian Farming, 2015)
Productivity in respect of cocoons and raw silk per hectare in tropicalzone is poor. High-yielding mulberry and silkworm varieties, appropriate technologies for silkworm rearing in warm and humid conditions and silk reeling technologies are required to improve productivity. The quality egg is foundation for production ofquality silk in bulk. Now-a-days all the sericulturally advanced countries are producing loose eggs due to its obvious advantages over sheet eggs for distribution among farmers.